FACTORS AFFECTING THE (PRODUCTION OF EXTRACELLULAR NEUTRAL PROTEASE) BY STREPTOMYCES MICROFLAVUS - Saadia, M. Hassanein; Hala M. Rifaat; Osama Hamed El-Said; Souad A. Saleh; Manal S. M. Selim (Arab Universities Journal of Agricultural Sciences, 2009)
In order to produce neutral protease from Streptomyces microflavus, it was cultivated in basal medium containing soluble starch, potassium nitrate, dipotassium hydrogen phosphate, magnesium sulphate, sodium chloride, calcium carbonate and ferrous sulphate. Protease production increased with decreasing the ratio of culture broth to vessel volume 1:5 and shaking at 150 rpm. Protease production was low when pH was < 5 or > 9. The productivity of protease decreased sharply when the incubation temperature increased from 30 to 450C. The maximum yield of protease was obtained at the third day of incubation. Soluble starch and yeast extract were the best carbon and nitrogen sources, respectively. Supplementation with calcium carbonate enhanced protease production. In addition, the dipotassium hydrogen phosphate was the best phosphorous source. Para chloromercuribenzoic acid and phenyl methylsulfonylfloride had significant inhibitory effect on protease production.